Gas Leakage Detection System with Alarming System - Baballe, Muhammad Ahmad; Bello, Mukhtar Ibrahim (Review of Computer Engineering Research, 2022)
This system aims to present a design that can automatically detect, alarm, and control gas leakage using an exhaust fan to suck the gas away from the premises where there is leakage. This system detects the nature of gas using LEDs (red and green). The alarm gives a sound when gas leakage is detected, the exhaust fan sucks the gas away from the premise, and the Liquid Crystal Display (LCD) indicates the system performance at any distortion condition. The Arduino UNO is used as the main controller of the system, and the buzzer is used as a means of notification. One of the prophylactic means to stop accidents related to this gas leakage is to mount a gas leakage monitoring device in susceptible places. The system will detect the leakage of liquefied petroleum gas (LPG) using a gas sensor and use the buzzer to alarm the industries, companies, or people about the leakage. The system also consists of two indicators (LEDs). The Green LED used in this research indicates no gas detection, that is, there is no gas leakage in the environment, and the red LED will indicate that there is gas leakage detected. The device is intended for use in household safety where appliances and heaters that use natural gas or LPG may be a source of risk. The system can also be used for other applications in the industries or companies that depend on LPG and natural gas in their operations.